Pedestal-to-wall 3D fluid transport simulations on DIII-D. (30th March 2017) - Lore, J.D.; Briesemeister, A.R.; Ferraro, N.M.; Frerichs, H.; Lyons, B.; McLean, A.; Park, J.-K.; Shafer, M.W.
Abstract: The 3D fluid-plasma edge transport code EMC3-EIRENE is used to test several magnetic field models with and without plasma response against DIII-D experimental data for even and odd-parity n = 3 magnetic field perturbations. The field models include ideal and extended MHD equilibria, and the vacuum approximation. Plasma response is required to reduce the stochasticity in the pedestal region for even-parity fields, however too much screening suppresses the measured splitting of the downstream T e profile. Odd-parity perturbations result in weak tearing and only small additional peaks in the downstream measurements. In this case plasma response is required to increase the size of the lobe structure. No single model is able to simultaneously reproduce the upstream and downstream characteristics for both odd and even-parity perturbations.